Impact Of Post-Transplantation Hypomagnesemia On Long-Term Graft And Patient Survival After Transplantation - Ofer Isakov; Bhanu K. Patibandla; Kenneth B. Christopher; Anil Chandraker; Tammy Hod (Karger Publishers, 2022)
BACKGROUND: Post-transplant hypomagnesemia is commonly observed among patients prescribed CNIs. METHODS: We conducted a retrospective single center analysis (2000-2013, N=726) to examine the association of hypomagnesemia with long-term patient and allograft outcomes in kidney transplant recipients. A median serum magnesium level of all measured magnesium levels from 1 month to 1 year post-transplant was calculated. RESULTS: For every increase in Mg of 0.1 mg/dL, the risk for either graft loss or death, overall survival and death with a functioning graft increased by 11%, 14% and 12% respectively (p < 0.01). In a multivariate model, patients with median Mg level ≥ 1.7 mg/dL had a reduced overall survival rate (HR 1.57, 95% CI 1.04-2.38, p = 0.033) compared to those with median Mg level < 1.7 mg/dL. This association was observed in subgroups of patients above 60 years old, in those who had a slow graft function (SGF) and in females. CONCLUSIONS: Post-transplant hypomagnesemia is associated with better patient and allograft survival up to 10 years post-transplant. This relationship remained significant after accounting for baseline allograft function, presence of slow graft function (SGF) and CNI trough levels.